Depositional age, provenance, and tectonic setting of the Neoproterozoic Sibao Group, southeastern Yangtze Block, South China - Wang, Wei; Zhou, Mei-Fu; Yan, Dan-Ping; Li, Jian-Wei (Precambrian research, 2012)
► The Sibao Group was deposited between ∼835 to 830 Ma. ► The Sibao Group had a mixed felsic-intermediate provenance composed of TTG-like, granitic, andesitic and felsic volcanic rocks. ► Detrital zircon age patterns reflect eroded/unexposed primary sources. ► Paleoproterozoic Weathering has been important in the source area significant K-metasomatism occurred after deposition. ► The Sibao Group formed in a back-arc foreland basin. The Sibao Group on the southeastern margin of the Yangtze Block of South China is composed mainly of flysch turbidites up to ca. 4000 m thick. Sandstones from the Sibao Group have intermediate to high SiO 2 (58.6–80.0 wt%, average 68.2 wt%) and Al 2O 3 wt% (7.4–20.6 wt%, average 15 wt%), typical of immature lithic varieties. Both sandstones and mudstones contain high K 2O (1.41–6.28 wt%) but extremely low Na 2O (0.03–1.49 wt%). Positive correlations between Al 2O 3 and Fe 2O 3 (T), TiO 2, MgO and K 2O, significant depletion of Ca, Na and Sr relative to upper continental crust and high PIA and pre-metasomatism CIA values suggest that intensive chemical weathering of the source area. Variable Cr/Th (3.9–37.0) and Co/Th (0.2–3.2) ratios indicate a source with predominant felsic and minor mafic components. Discrimination diagrams involving Ti, Al, Fe, La, Th, Sc, Hf and Co reveal the source with multiple lithologies consisting mainly of TTG-like, granitic, andesitic and felsic volcanic rocks. Predominant detrital zircons have Neoproterozoic ages from 822 to 980 Ma, whereas the remaining zircons define two age groups at 1.35–2.22 Ga and 2.32–2.86 Ga. Twenty-six of the youngest grains have a weighted mean age of 835.3 ± 3.6 Ma, tentatively interpreted as the maximum depositional age of the Sibao Group. Neoproterozoic zircon grains have variable 177Hf/ 176Hf ratios (0.281194 to 0.282564) and ɛ Hf(t) values (−35.9 to 9.8), indicative of the involvement of juvenile and ancient recycled components. The 1.4 and 1.8 Ga zircon grains have variable 177Hf/ 176Hf ratios (0.280947–0.281874), probably reflecting the growth of the supercontinent Columbia and suggesting that the Yangtze Block was separated from Columbia as an independent terrane at around 1.4 Ga. The complicated provenance involving felsic to intermediate rocks and Neoproterozoic juvenile to Neoarchean mature materials suggests that the Neoproterozoic Sibao Group was deposited in a back-arc foreland basin related to the northward (present coordinate) subduction of an oceanic lithosphere beneath the southeastern Yangtze Block.